Expressão de p63 e p53 em tumores mamários mistos de cadelas - Bertagnolli, Angélica Cavalheiro (2006)
The p63 protein is expressed in the nuclei of the mammary myoepithelial cells and has synergisms or antagonisms with p53 tumor suppressor protein. The immunohistochemistry expression of p63 was studied for access the role of myoepithelial cells in histogenesis of the mixed tumors. Additionally, the possible association between p63 and p53 for access the biological aspects of this tumors was evaluated. Four specimens of the normal gland, 20 benign mixed tumors, 35 carcinomas in mixed tumors and 11 tubulopapilary carcinomas were evaluated. Myoepithelial cells forming layers periductals/periacinars continuous were reactive for protein p63 in normal gland and in benign mixed tumor. The carcinomas in mixed tumors and 72.7% (8/11) tubulopapilary carcinomas were reactive for p63. In the mixed tumors star and spindle shaped cells were reactive for p63. The p53 protein was expressed in 20.0% (4/20), 28.6% (10/35) and 36.7% (4/11), benign mixed tumors, carcinoma in mixed tumors and tubulopapilary carcinomas, respectively. There was not relation between p63 and p53 expression in none type of tumor. The present study point the participation of the mioepithelial cells in the histogenesis of the mixed tumors. The decrease in p63 expression in the basal myoepithelial cells of the carcinomas may be important for tumoral progression.